Assessment of composite materials in advance application: A mini overview. (2021) - Fayomi, O.S.I; Okwilagwe, O.; Agboola, O.; Oyedepo, S.O; Popoola, A.P.I
Abstract: The construction industry is one of the significant sources of greenhouse gas (GHG) emissions globally. Scientists are searching for advanced materials that can replace scarce natural resources, cumbersome and costly materials, and minimize CO2 emission by reducing the cement content in building materials with more eco-friendly materials. These advanced materials have become a crucial research topic and a significant area of interest due to their advantageous properties and versatile applications. This article provides an overview of the features, cost, performance, environmental impact, and relevance of composites in the building sector.